If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 5x + 12 Reorder the terms: 3 = 12 + 5x Solving 3 = 12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + -5x = 12 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + -5x = 12 + 0 3 + -5x = 12 Add '-3' to each side of the equation. 3 + -3 + -5x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 12 + -3 -5x = 12 + -3 Combine like terms: 12 + -3 = 9 -5x = 9 Divide each side by '-5'. x = -1.8 Simplifying x = -1.8
| t+(2t+4)=-5 | | 8x/3-5x/4=-13 | | 5/25=y/85 | | -(5b+5)-5=1-(5b-1) | | -36=4w | | 11=3-7x | | X^3-2X+0.5=0 | | X^3-2X-0.5=0 | | 22=2c | | -2(2(2)-4)=-4(-2+2) | | 4x^2+9x-2=0 | | .90x+.52(2-x)=.10(-118) | | 3x-16cm=200cm | | 7x+2[3(1-x)]=14 | | 3(t+2)-(3t-3)=2(3t-4)-13 | | 3(t+2)-(3t-3)=2 | | 64=8n | | (x+3)-2c-(1-3x)=2 | | 6w^3-28w+16=0 | | .5y+2=.8y-.3 | | x=4x+96 | | 2w-6m=50m | | -8(-1)-(3(-1)+6)=4+-1 | | -7=3(x-5)-x | | x-13x+10x=50-6 | | -17+2x=6-x | | X=10+-2X | | (x+1)(x+2)=2x | | 6x+14=2x | | 0.25(q-12)=4 | | 10n=4n+5+5n | | 2x+1+5X-11=4X |